A numerical study on the performance of a converging thermoelectric generator system used for waste heat recovery. (15th July 2020) - Luo, Ding; Wang, Ruochen; Yu, Wei; Zhou, Weiqi
Highlights: A converging thermoelectric generator system is proposed and fabricated. A multiphysics fluid-thermoelectric coupled field numerical model is proposed. Comparison between converging and traditional heat exchanger structures is performed. The converging thermoelectric generator induces more even temperature distribution. The multiphysics model is verified by the experimental test. Abstract: Structure-based optimization is an effective approach to improve the performance of thermoelectric generators. Aiming to increase the heat transfer and hot side temperature of the heat exchanger, a converging heat exchanger design is developed in this study. Furthermore, a multiphysics fluid-thermoelectric coupled field numerical model is proposed, which is used to perform comprehensive numerical simulations to evaluate the behaviour of the thermoelectric generator system. The results indicate that the converging thermoelectric generator system generates a higher output power, induces a lower backpressure power loss, and has a more uniform temperature distribution than the conventional structure. The output power of the converging thermoelectric generator system is approximately 5.9% higher than that of the conventional system at an air temperature of 550 K and an air mass flow rate of 60 g/s. Moreover, the power increment provided by the converging design increases with increasing air temperature and decreasing air mass flow rate. The maximum deviation in the output power between the numerical and experimental results is 2.4%, which validates the performance of the multiphysics fluid-thermoelectric coupled field numerical model. This work provides new insights for numerical investigations of thermoelectric generator systems and presents a novel concept for optimizing the exhaust gas channel of a heat exchanger.